(untitled) (Global Conference on Medical and Health Sciences, 2026)
The rapid digitalization of healthcare systems has led to the widespread adoption of electronic health records, telemedicine platforms, and interconnected medical devices, significantly improving healthcare delivery. However, this transformation has also introduced critical cybersecurity challenges, particularly concerning the protection of sensitive patient data. Healthcare information systems have become prime targets for cyberattacks due to the high value of medical data and the complexity of digital infrastructures. This study aims to evaluate the major cybersecurity challenges in healthcare systems, assess their impact on patient data protection, and explore strategies for mitigating associated risks. A mixed-methods approach was employed, combining quantitative analysis of cybersecurity incidents with qualitative insights from healthcare IT professionals. The findings indicate that healthcare systems face increasing threats from ransomware, data breaches, and unauthorized access, which can compromise patient privacy and disrupt clinical operations. Additionally, vulnerabilities related to outdated systems, lack of staff training, and insufficient regulatory compliance contribute to cybersecurity risks. The study concludes that strengthening cybersecurity frameworks, implementing advanced encryption technologies, and enhancing workforce awareness are essential for protecting healthcare data in the digital era.